An explicit finite element modelling method for masonry walls under out-of-plane loading. (15th April 2016) - Noor-E-Khuda, Sarkar; Dhanasekar, Manicka; Thambiratnam, David P.
Highlights : An explicit finite element method is presented for out-of-plane loaded wall structures. Homogenised masonry properties are successfully incorporated into shell elements. Predicted out-of-plane response of walls agree well with experimental results. Solid and perforated walls of varied aspect ratios, supports and pre-compression examined. Sensitivity of key parameters of walls to its ductility and failure is reported. Abstract: An explicit finite element modelling method is formulated using a layered shell element to examine the behaviour of masonry walls subject to out-of-plane loading. Masonry is modelled as a homogenised material with distinct directional properties that are calibrated from datasets of a "C" shaped wall tested under pressure loading applied to its web. The predictions of the layered shell model have been validated using several out-of-plane experimental datasets reported in the literature. Profound influence of support conditions, aspect ratio, pre-compression and opening to the strength and ductility of masonry walls is exhibited from the sensitivity analyses performed using the model.